Integrated mechanical computing for autonomous soft machines - Byun, Junghwan; Pal, Aniket; Ko, Jongkuk; Sitti, Metin (Nature Publishing Group, 2024)
Mechanical computing offers a new modality to formulate computational autonomy in intelligent matter or machines without any external powering or active elements. Transition (or solitary) waves, induced by nonreciprocity in mechanical metamaterials comprising a chain of bistable elements, have proven to be a key ingredient for dissipation-free transmission and computation of mechanical information. However, advanced processing of mechanical information in existing designs is hindered by its dissipation when interacting with networked logic gates. Here, we present a metamaterial design strategy that allows non-dispersive mechanical solitary waves to compute multi-level cascaded logic functions, termed 'integrated mechanical computing', by propagating through a network of structurally heterogeneous computing units. From a perspective of characteristic potential energy, we establish an analytical framework that helps in understanding the solitary wave-based mechanical computation, and governs the mechanical design of key determinants for realizing cascaded logic computation, such as soliton profile and logic elements. The developed integrated mechanical computing systems are shown to receive, transmit and compute mechanical information to actuate intelligent soft machine prototypes in a seamless and integrated manner. These findings would pave the way for future intelligent robots and machines that perform computational operations between various non-electrical environmental inputs. Many mechanical computation platforms developed till date lack a rational design strategy and have limited computational functions, such as stand-alone single logic gates, or deformation/transition behaviors. Byun at al. have reported a systematic design principle for integrated mechanical computing that enables the electronics-free design of autonomous and intelligent soft machines, which are seamlessly integrated.